CTCF: from insulators to alternative splicing regulation - Kornblihtt, Alberto Rodolfo (2012)
The zinc-finger DNA-binding protein CTCF has been known for being a constituent of insulators. A recent paper in Nature reports an unforeseen intragenic role for CTCF that links DNA methylation with alternative splicing. By binding to its target DNA site placed within an alternative exon, CTCF creates a roadblock to transcriptional elongation that favors inclusion of the exon into mature mRNA. DNA methylation prevents CTCF binding, which releases pol II transient blockage and promotes exon exclusion.